Satisfaction of students and graduates of pedagogy in physical education, with respect to the training received in the area of contact with nature (Revista horizonte, 2021)
The  new  pedagogical  tendencies  currently  occurring  in  Higher  Education  have  led  to  a  rethinking  of university  curricula,  since  the  heterogeneity  of  the  offer  of  careers  in  institutions  is  diverse, generatingthe urgent  need  to  give  public  faith  of  the  capacities  of  the  graduates  for  their  professional practice  through processes of quality assurance. Objective: to establish the satisfaction of students and graduates of the career of Pedagogy in Middle Education, regarding the training received in the area of contact with nature. Method: Non-experimental  cross-sectional  and  descriptive  scope.  The  selection  of  the sample  was  non-probabilistic assignment.  Participants:  65  students  and  graduates  (21  women  and  44 men).  Instruments:  Likert  scale  and open interview. Results: Differences of measurement are shown in the total scale and the gender dimensions with  respect  to  the  perceptions  between  men  and  women.  Males  with  a  Mean  (115.9  points)  and  with significance (t = 2.065, p